Verification of structural integrity and cooling performance of DRCS cabinet in power plant - Seung-Hun Song (Advances in Mechanical Engineering, 2020)
The digital rod control system (DRCS) is an important component in nuclear power plants. Thus, the structural integrity of the isolation cabinet of the DRCS should be verified, considering the seismic loading and cooling performance of the heating source of electric equipment. In general, the structural safety and functionality of the DRCS are verified through ground excitation and flow experiments. Numerical structural analysis and CFD analysis provide preliminary assessments of dynamic behavior and temperature distribution of the cabinet in order to establish guidelines for designing experiments. This also reduces time, cost, and design cycles involved in the experimentation. Response spectrum analysis was adopted in ANSYS for seismic analysis, which gives the peak response of the structure. The analysis was performed based on required response spectra (RRS), which envelop the floor response spectra (FRS). The maximum stresses are less than the allowable stresses, and the deflections meet the requirements. Electric equipment should operate within a limited temperature range for acceptable reliability. In the direct heat removal approach, six fans are installed as heat sink and air is forced through the heat sink by the fan. The cabinet and internal modules should be designed such that adequate ventilation with the fans is provided to maintain the temperature difference between the inside and outside within 5°C. Flow and thermal analyses were carried out by a CFD program, Icepak. As a result of this analysis, the number and the capacity were determined to meet the design requirement.